Model Kepemimpinan Transformasional Bidang Pendidikan dalam Perspektif Hadist - Rohimat, Sonny; Siti Syifa Fauziah; Syarifudin, Encep; Lugowi, Rifyal Ahmad (JoIEM (Journal of Islamic Education Management), 2025)
The urgency of leadership in the field of education is reinforced by the condition that educational units are one of the most important organizations in society. This study aims to analyze the relevance of the transformational leadership model in educational management based on the perspective of the hadith. The study was conducted through a literature review of several hadiths related to leadership. Transformational leadership has four dimensions, namely idealized influence, intellectual stimulation, individualized consideration, and inspirational motivation. The four dimensions of transformational leadership are related to a number of hadiths of the Prophet Muhammad. The results of the analysis show that the dimensions of transformational leadership are in line with the leadership carried out or exemplified by the Prophet. Thus, transformational leadership is considered relevant for use in implementing Islamic education management. Urgensi kepemimpinan dalam bidang pendidikan diperkuat dengan kondisi yang terjadi bahwa satuan pendidikan merupakan salah satu organisasi yang sangat penting dalam masyarakat. Penelitian ini bertujuan untuk menganalisis relevansi model kepemimpinan transformasional dalam manajemen pendidikan berdasarkan perspektif hadis. Penelitian dilakukan melalui kajian literatur terhadap beberapa hadis yang berkaitan dengan kepemimpinan. Kepemimpinan transformasional memiliki empat dimensi yaitu idealized influence; intellectual stimulation; individualized consideration; dan inspirational motivation. Keempat dimensi kepemimpinan transformasional memiliki keterkaitan dengan sejumlah hadis Rasulullah saw. Hasil analisis menunjukkan bahwa dimensi-dimensi kepemimpinan transformasional selaras dengan kepemimpinan yang dilakukan atau dicontohkan oleh Rasulullah saw. Dengan demikian maka kepemimpinan transformasional dinilai relevan untuk digunakan dalam menjalankan manajemen pendidikan Islam.